Combine Effect of Harjod Vanvasi Oil and Harjod Vanvasi Capsule in the management of Sandhigata Vata w.s.r. to joint Pain An Open Level Randomized Clinical Trial: The effectiveness of Harjod Vanvasi Oil and Capsule in managing Sandhigata Vata (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The body attains it’s a healthy state when there is an equilibrium of Dosha, Dhatu, Mala in thebody. Vata Dosha plays an important role in the maintenance of this equilibrium. However, it’s vitiationleads to numerous disorders one of which is Sandhigata Vata which has become common trouble forpeople in the present scenario irrespective of age. The reason is obvious a disturbed diet and asedentary lifestyle. When it comes to balance Vata in the body Ayurveda offers diverse medicationsmodalities and therapies. One such magnificent medicine has been prepared i.e. Harjod Vanvasi Oil forlocal application and Harjod Vanvasi Capsule for oral intake for thirty days. The patients were enrolledon the basis of particular symptoms and it’s severity was recorded, the symptoms were Sandhi Shoola,Sandhi Shotha, Aakunchana Prasaran Vedana, Sandhigraha and Sparshasahyata. Patients were alsoadvised to avoid Vata Vardhak Ahaar and Vihaar. The follow-up was taken on the 15th day. Thereasonable result was observed with subsidation of symptoms at the end of the study i.e. aftercompletion of thirty days of medication along with oil application. The result was concluded byexamination of the patients as well as based on a conversation with the patients.